Karakteristik Pertanggungjawaban Pidana Korporasi dalam Kasus Tindak Pidana Lingkungan Hidup - Irohman Syaputra; Aturkian Laia (INDO PUBLISHING, 2026)
Corporate activities drive economic growth but also serve as a primary source of environmental degradation in Indonesia, including waste pollution and land fires. This normative legal research examines the characteristics of corporate criminal liability in environmental offenses using statutory, conceptual, and case approaches. The analysis focuses on liability characteristics, positive law regulations, and enforcement obstacles. The results indicate that corporate liability is both derivative and autonomous, where institutional fault is construed as a systemic failure in policy and environmental compliance culture. Although Law No. 32/2009 and Supreme Court Regulation No. 13/2016 are established, implementation remains hindered by mens rea proof difficulties, judicial disparity, and weak judgment execution. This study recommends strengthening corporate fault doctrine through a corporate compliance failure model.